Blow-Up of Solutions to a Novel Two-Component Rod System - Shengrong Liu; Zhengguang Guo; Weiming Wang (Abstract and Applied Analysis)
We consider a novel two-component rod system which is closely connected to the shallow water theory. The present work is mainly concerned with the blow-up mechanism of strong solutions; we establish new conditions in view of some special classes of initial value to guarantee finite time blow-up of solutions.